2021
DOI: 10.1111/odi.14081
|View full text |Cite
|
Sign up to set email alerts
|

Psychological profile and α‐amylase levels in oral lichen planus patients: A case–control preliminary study

Abstract: Objective: To investigate psychological (anxiety, depression, and stress) and salivary (flow and concentration of α-amylase) profile associated with oral lichen planus. Materials and methods:A case-control preliminary study with oral lichen planus patients and age-gender matched controls was conducted. The participants underwent psychological tests (Beck depression and anxiety inventories and perceived stress scale) and saliva collection to determine the unstimulated salivary flow and α-amylase levels at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A study was also published, in which the search for factors common to depressive disorders and lichen planus highlighted two genes (NCAM1 and CD4) identified as common to the pathomechanism of both disorders [ 62 ]. Patients with the oral form of lichen planus were also found to have higher salivary alpha-amylase levels in those with depressive disorders, which may be an interesting further line of research into the risk markers for the development of depressive disorders [ 63 ]. However, the most interesting study from the point of view of inflammatory theory and depressive disorders is the one that found increased levels of stress, mast cells and salivary nitric oxide in patients with depressive disorders and lichen planus [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study was also published, in which the search for factors common to depressive disorders and lichen planus highlighted two genes (NCAM1 and CD4) identified as common to the pathomechanism of both disorders [ 62 ]. Patients with the oral form of lichen planus were also found to have higher salivary alpha-amylase levels in those with depressive disorders, which may be an interesting further line of research into the risk markers for the development of depressive disorders [ 63 ]. However, the most interesting study from the point of view of inflammatory theory and depressive disorders is the one that found increased levels of stress, mast cells and salivary nitric oxide in patients with depressive disorders and lichen planus [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the studies conducted on the association between psychological disorders and OLP are contradictory. Simoura JAdS et al showed a significant correlation between depression, anxiety, and stress, and OLP [42]. The systematic review and metaanalysis by De Porras-Carrique T et al showed a strong association between OLP and mental disorders.…”
Section: Discussionmentioning
confidence: 97%
“…There are few studies that have investigated salivary α-amylase activity in patients with OLP, and their results are contradictory. The results of the study by Simour JAdS et al showed increased salivary α-amylase activity 30 min after awakening in patients with OLP (determined at three time points) [ 42 ]. Pippi R et al showed no statistically significant difference in daily fluctuation or production of salivary α-amylase between patients with OLP and control subjects (determined at three time points) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies conducted on the association between psychological disorders and OLP are contradictory. Simoura JAdS et al showed a significant correlation between depression, anxiety, and stress, and OLP [ 42 ]. The systematic review and meta-analysis by De Porras-Carrique T et al showed a strong association between OLP and mental disorders.…”
Section: Discussionmentioning
confidence: 99%